2014
DOI: 10.1590/s1415-47572014000300016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mutagenicity and antimutagenicity of Ziziphus joazeiro Mart. bark in the micronucleus assay

Abstract: The aim of this study was to evaluate the mutagenicity (clastogenicity/aneugenicity) of a glycolic extract of Ziziphus joazeiro bark (GEZJ) by the micronucleus assay in mice bone marrow. Antimutagenic activity was also assessed using treatments associated with GEZJ and doxorubicin (DXR). Mice were evaluated 24–48 h after exposure to positive (N-nitroso-N-ethylurea, NEU - 50 mg.kg−1 and DXR - 5 mg.kg−1) and negative (150 mM NaCl) controls, as well as treatment with GEZJ (0.5–2 g.kg−1), GEZJ (2 g.kg−1) + NEU and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…The putative antioxidant activity of one or more of the active compounds of C. langsdorffii, including two major flavonoid heterosides (quercitrin and afzelin) may explain the effect of this plant on DXR-induced genotoxicity (Alves et al, 2013). More recently, the absence of genotoxicity of the tincture and two sources of oils of H. annuus was observed in the bone marrow of Swiss albinus mice using micronucleus assay, but indications of antigenotoxic effects were related to combination treatment with the tincture and DXR, suggesting a partial protective mechanism against DXR-induced genotoxic effects (Boriollo et al, 2014a). Finally, the nongenotoxicity of Z. joazeiro and its antigenotoxic effects when administered together with DXR were also related as shown by micronucleus assay in the bone marrow of Swiss albinus mice (Boriollo et al, 2014b).…”
Section: Mnpces (N)mentioning
confidence: 99%
See 2 more Smart Citations
“…The putative antioxidant activity of one or more of the active compounds of C. langsdorffii, including two major flavonoid heterosides (quercitrin and afzelin) may explain the effect of this plant on DXR-induced genotoxicity (Alves et al, 2013). More recently, the absence of genotoxicity of the tincture and two sources of oils of H. annuus was observed in the bone marrow of Swiss albinus mice using micronucleus assay, but indications of antigenotoxic effects were related to combination treatment with the tincture and DXR, suggesting a partial protective mechanism against DXR-induced genotoxic effects (Boriollo et al, 2014a). Finally, the nongenotoxicity of Z. joazeiro and its antigenotoxic effects when administered together with DXR were also related as shown by micronucleus assay in the bone marrow of Swiss albinus mice (Boriollo et al, 2014b).…”
Section: Mnpces (N)mentioning
confidence: 99%
“…In this context, recent studies indicated protective effects of extracts from Aegle marmelos (Venkatesh et al, 2007), Copaifera langsdorffii (Alves et al, 2013), Helianthus annuus (Boriollo et al, 2014a), and Ziziphus Presidente Prudente, SP, Brazil) and evaporation bottle (RV 10.85 Evaporation Flask, NS 29/32-2L, IKA  Works, Inc., USA). The final product was transferred to a reaction bottle 1 L (SCHOTT  DURAN  ) and kept at −20 °C for 24 hours in order to evaluate the freezing of the final product and the efficacy of the solvent evaporation process (Boriollo et al, 2014a, b).…”
Section: Phytotherapeuticmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the folkloric practices have been empirically validated now. The verified health benefits include antioxidant (Olajuyigbe and Afolayan 2011 ; Chen et al 2014c ), anti-inflammation (Yu et al 2012 ), antibacterial and antifungal (Ghazghazi et al 2014 ), antiulcerogenic (Wahida et al 2007 ), immunomodulatory (Chen et al 2014a ), diabetes ameliorating (Goli-malekabadi et al 2014 ), hepatoprotective (Kwape et al 2013 ; Yue et al 2014 ), hematopoietic (Chen et al 2014b ), antimutagenic (Boriollo et al 2014 ), cytotoxic (Jafarian et al 2014 ), and sedative-hypnotic (Gao et al 2013a ). The plant parts conferring the biological effects are diverse such as leaves (Nisar et al 2007 ; Kwape et al 2013 ; Goyal et al 2013 ), fruits (Plastina et al 2012 ; Chen et al 2014a , b , c ), seeds (Cao et al 2010 ; San et al 2013 ; Gao et al 2013a ), bark (Olajuyigbe and Afolayan 2011 ; Boriollo et al 2014 ) and root (Rao et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these characteristics the micronucleus assay in rodent bone marrow has long been used in the analysis of genotoxicity for many herbal medicines, especially those of pharmaceutical interest. Highlights are the analysis of Boriollo et al [14] with Ziziphus joazeiro Martius; Mahon et al [15] with Dilodendron bipinnatum Radlk; Oliveira et al [16] with Calophyllum brasiliense; Shin et al [17] with Polygala tenuifolia and Tolentino et al [18] with Rubus niveus.…”
Section: Introductionmentioning
confidence: 99%